2002
DOI: 10.1002/em.10039
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic activity and mutational specificity of antiprotozoal drugs with and without nitrite treatment

Abstract: We examined the mutagenic activities of six antiprotozoal drugs (three diaminopyrimidine compounds [pyrimethamine, diaveridine, and trimethoprim] and three 8-aminoquinoline derivatives [primaquine, pentaquine, and pamaquine]) in Escherichia coli WP2uvrA/pKM101 and Salmonella typhimurium TA100 and TA98 with and without nitrite treatment. The diaminopyrimidine compounds showed no mutagenic activity under any condition in any strain. The 8-aminoquinoline derivatives after nitrite treatment at 5-20 mM for 5 min at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The drug was mutagenic in both microbial strains, suggesting that PQ is a nitrite-reacting mutagen precursor where the secondary amino group plays a key role [116].…”
Section: Other Biological Effects Of Pqmentioning
confidence: 98%
“…The drug was mutagenic in both microbial strains, suggesting that PQ is a nitrite-reacting mutagen precursor where the secondary amino group plays a key role [116].…”
Section: Other Biological Effects Of Pqmentioning
confidence: 98%
“…DVD is used in combination with sulfaquinoxlaine as an antiprotozoal agent in animals for the prophylaxis and treatment of coccidiosis and leukocytozoonosis (Cirioni et al, 1997;Patthy, 1983). TMP and DVD were not mutagenic in the umn test bacterial reverse mutation tests in the presence and absence of S9 mix (Ono et al, 1997;Ono-Ogata et al, 2002). However, DVD was found to be genetoxic in mammalian cells in vitro and in vivo, but TMP was not (Ono et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Ono-Ogata et al (2002) found that the diaminopyrimidine pyrimethamine has no mutagenic e¡ect in E. coli WP2uvrA/ pKM101 and Salmonella typhimurium TA 100 and TA98. Nevertheless, positive results have been reported with pyrimethamine in vitro cytogenetic assays, inducing both CA and SCE in human lymphocyte cells (Egeli and Erdogan, 1991;Egeli, 1998).…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the genotoxicity of pyrimethamine, it should be recalled that, based on the available data from open literature and reports from manufacturers, the results obtained with this drug are rather controversial because, both in bacterial and mammalian cells, positive and negative e¡ects have been reported. In this connection, pyrimethamine showed no mutagenic activity in bacterial test system (Ono-Ogata et al, 2002). Furthermore, Mailhes et al (1993) reported that pyrimethamine did not induce aneuploidy in the oocytes of exposed mice.…”
Section: Introductionmentioning
confidence: 96%